Grand SLAM study protocol: a prospective randomised multicentre study of shortened versus standard duration adjuvant immune checkpoint inhibition for stage IIB-C, III and IV cutaneous melanoma - Ejder, Patric; Jespersen, Henrik; Hernberg, Micaela; Ny, Lars; Carneiro, Ana; Ellegård, Sander; Mattila, Kalle; Bagge Olofsson, Roger; Fountoukidis, Georgios; Brandberg, Yvonne; Mandala, Mario; O’Carrigan, Brent; et al. (Springer Science and Business Media LLC, 2026)
Background: Adjuvant treatment with PD-1 inhibitors for 12 months has been the established standard of care for patients with resected stage IIB-IV cutaneous melanoma. In other solid tumours (e.g. breast and colorectal), a shorter duration of adjuvant chemotherapy has been shown to be non-inferior with improved toxicity profile. More recently, neoadjuvant immunotherapy with immune checkpoint inhibitors for clinically detectable stage III and stage IV disease has been introduced. There is no clear biological rationale for the chosen duration, and no studies have investigated duration of adjuvant treatment with immune checkpoint inhibitors. A reduced duration of adjuvant therapy could lead to less toxicity from reduced drug exposure, patients returning to normal life sooner, significantly lower drug costs and better healthcare resource utilization. There remains significant interest from patients and clinicians to address this important question.
Methods: Grand SLAM is a prospective phase III randomised, controlled international multi-centre non-inferiority study. The primary objective is to investigate if short (6 months) has equal efficacy as long (12 months) duration of (neo-)adjuvant immune checkpoint inhibition in relation to distant metastasis-free survival and relapse-free survival at landmark analysis at 2 years. After radical surgery of stage IIB-C, III or IV cutaneous melanoma, patients are randomly assigned 1:1 to short or long adjuvant treatment with either nivolumab or pembrolizumab. Patients who have received neoadjuvant treatment with major pathological response are excluded. The sample size of 1,880 patients was determined based on a non-inferiority margin of 4%, a significance level of 0.045 and 80% statistical power. An interim analysis will be conducted when 2/3 of patients are accrued. Biomarkers and the role of food supplements for relapse (MelKo) will be investigated in prespecified substudies.
Discussion: This is the first randomised study to assess a shorter duration of adjuvant anti PD-1 antibody in cutaneous melanoma patients. As of March 2026, the study is recruiting patients in the Nordic countries. Centres in other countries will open shortly.
Trial registration: NCT06488482. Date of registration: 2024-06-10.
Supplementary Information: The online version contains supplementary material available at 10.1186/s12885-026-15924-4.
Keywords: Adjuvant; Cutaneous melanoma; Immunotherapy; Neoadjuvant.